Analysis of The Effect of Service Quality and Health Facilities Patient Satisfaction At Bethesda Hospital Gunungsitoli City - Berlian Telaumbanua; Nuri Aslami; Aqwa Naser Daulay (Dinasti Publisher, 2024)
Patient satisfaction will be reflected in how far their level of trust in medical procedures and how clear the information provided by the medical team is. The better standardization of service quality fulfillment and facilities at the hospital, the patient satisfaction will increase. Therefore, this study aims to determine the effect of service quality and facilities on patient satisfaction at Bethesda Hospital, Gunungsitoli City. This research method applies a quantitative approach with associative analysis through multiple linear regression analysis testing techniques by utilizing the SPSS 23 analysis tool. The sample used in this study were Bethesda Hospital patients using the Slovin method. The results of the study prove that the variables of service quality and facilities have a positive and significant effect on patient satisfaction at Bethesda Gunungsitoli Hospital. The results obtained show that improving the quality of services and facilities simultaneously has an influence on patient satisfaction of RSU Bethesda Gunungsitoli city.